2003
DOI: 10.1093/jn/133.11.3449
|View full text |Cite
|
Sign up to set email alerts
|

Low Preconception Body Mass Index Is Associated with Birth Outcome in a Prospective Cohort of Chinese Women

Abstract: Low maternal prepregnancy BMI is associated with adverse birth outcomes, but the BMI at which risk increases is not well defined. We assessed whether the relationship between prepregnancy BMI and birth outcomes is influenced by the extent to which mothers were underweight in a prospective study in Anhui, China. The women (n = 575) were 20-34 y old, married, nulliparous and nonsmokers. All measures of infant growth increased with increasing maternal BMI until a plateau was reached at a BMI of 22-23 kg/m2. Infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 27 publications
7
76
1
6
Order By: Relevance
“…This finding is consistent with the results of other studies. [22][23][24] As with many other observational studies, this study was prone to errors, including selection bias, misclassification and confounding. First, selection bias may have occurred because women delivering at a tertiary hospital may already have a higher prevalence of risk factors compared to women delivering at other types of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of other studies. [22][23][24] As with many other observational studies, this study was prone to errors, including selection bias, misclassification and confounding. First, selection bias may have occurred because women delivering at a tertiary hospital may already have a higher prevalence of risk factors compared to women delivering at other types of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported an association between insufficient weight gain in pregnancy and increased risk of low birth weight, intrauterine growth restriction, and prematurity 4,5 . Meanwhile, excessive weight gain has been associated with increased incidence of diabetes mellitus and gestational hypertension, cesarean delivery, fetal macrosomia, perinatal morbidity and mortality, postpartum weight retention, and childhood obesity 6,7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies from India and other parts of the world have demonstrated the role of pre-pregnant weight and weight gain during pregnancy on the fetal size (Raman et al, 1995;Ehrenberg et al, 2003;Ronnenberg et al, 2003). However, very few studies from India have explored the role of components of maternal weight, that is, fat mass and lean mass on the infant's birth weight.…”
Section: Introductionmentioning
confidence: 99%